ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU - Meliala, Yos Horta (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The purpose of this study was to (i) identify and analyze the effect of the dimensions of service quality that consists of physical evidence, reliability, responsiveness, assurance and empathy to the satisfaction of the guests who come and stay at the Hotel Borobudur Asri and (ii) to identify and analyze Dimensions in service quality the most dominant effect on guest satisfaction satisfaction that come and stay at the Hotel Borobudur Asri. The research was conducted at Hotel Borobudur Asri, with a population of 100 with a total sampling technique sampling, which means that all members of the population sampled as many as 100 people. Analysis of the data used is descriptive research to explain the data and a description of the study, while for analyzing quantitative data using a multiple linear regression analysis.The research proves that the simultaneous results of this study prove the conjecture H0 is rejected and H1 accepted that physical evidence, reliability, responsiveness, assurance and empathy simultaneously significantly positive effect on the satisfaction of the guests who come and stay at the Hotel Borobudur Asri. Partially tangibles, reliability, responsiveness, assurance and empathy has been implemented well in achieving guest satisfaction that come and stay at the Hotel Borobudur Asri. Based on the results of the study found that the dimensions of service quality based on the reliability of the dominant influence on the satisfaction of the guests who come and stay at the Hotel Borobudur Asri. This means that guests have been able to understand that the perceived satisfaction is determined by all employees in providing services to work quickly in the service process and provide service with no favoritism (fair and do not discriminate) to give confidence to the guests a quality service.